Implications of the Reykjavik summit on its twentieth anniversary : conference report - Drell, Sidney D. (Sidney David), 1926-2016; Shultz, George P., 1920-2021 (Hoover Institution Press publication ;, 2007)
Drawn from presentations at the Hoover Institution's conference on the twentieth anniversary of the Reykjavik summit, this collection of essays examines the legacy of that historic meeting between President Reagan and Mikhail Gorbachev. The contributors discuss the new nuclear era and what the lessons of Reykjavik can mean for today's nuclear arms control efforts.